2021
DOI: 10.3390/cancers13020256
|View full text |Cite
|
Sign up to set email alerts
|

Gain/Amplification of Chromosome Arm 1q21 in Multiple Myeloma

Abstract: Multiple myeloma (MM), a plasma cell neoplasm, is an incurable hematological malignancy characterized by complex genetic and prognostic heterogeneity. Gain or amplification of chromosome arm 1q21 (1q21+) is the most frequent adverse chromosomal aberration in MM, occurring in 40% of patients at diagnosis. It occurs in a subclone of the tumor as a secondary genomic event and is more amplified as the tumor progresses and a risk factor for the progression from smoldering multiple myeloma to MM. It can be divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 93 publications
(105 reference statements)
2
49
0
1
Order By: Relevance
“…First, by combining WGS and 3D genome data we found that genetic amplification disrupts a large proportion of the chromatin structure throughout the chr1q arm. This level of disruption likely reflects contribution of multiple mechanisms to structural changes in chr1q 46 , including isochromosome formation 47 , hypoxia-driven tandem duplications 48 , jumping translocations 4 , chromothripsis 49 , chromoplexy 50 , and combination of the above 51 . Nevertheless, we detected four main blocks of co-amplification (hyper-domains) which are the product of distinct amplification patterns and retain their overall chromatin structure across MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, by combining WGS and 3D genome data we found that genetic amplification disrupts a large proportion of the chromatin structure throughout the chr1q arm. This level of disruption likely reflects contribution of multiple mechanisms to structural changes in chr1q 46 , including isochromosome formation 47 , hypoxia-driven tandem duplications 48 , jumping translocations 4 , chromothripsis 49 , chromoplexy 50 , and combination of the above 51 . Nevertheless, we detected four main blocks of co-amplification (hyper-domains) which are the product of distinct amplification patterns and retain their overall chromatin structure across MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, by combining WGS and 3D genome data we found that genetic amplification disrupts a large proportion of the chromatin structure throughout the chr1q arm. This level of disruption likely reflects contribution of multiple mechanisms to structural changes in chr1q (31), including isochromosome formation (32), hypoxia-driven tandem duplications (33), jumping translocations (5), chromothripsis and chromoplexy (34), and combination of the above (35). Nevertheless, we detected four main blocks of co-amplification (hyper-domains) which are the product of distinct amplification patterns and retain their overall chromatin structure across MM patients.…”
Section: Discussionmentioning
confidence: 77%
“…However, it should be noted that many other genes at the 1q21 locus could be associated with poor prognosis and resistance to chemotherapy [14] . 1q21+ is also observed in non-anaplastic MM and is likely to be associated with the disease progression of MM [15] . Moreover, it was recently reported that 1q21+ is strongly associated with MYC rearrangement, which is associated with poor prognosis in MM [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 96%